Nutrition knowkledge, attitude and practice of college sportsmen - Nazni, P.; Vimala, S. (Asian Journal of Sports Medicine, 2010)
Purpose: Nutrition is an important component of any physical fitness program. The main dietary goal for active individuals is to obtain adequate nutrition to optimize health fitness and to increase sports performance. The present study aims to assess the nutrition knowledge, attitude and practice among the selected athletes.